Ferroptosis and endoplasmic reticulum stress in rheumatoid arthritis - Ao, Qin; Hu, Huan; Huang, Ying (Frontiers in Immunology, 2024)
Ferroptosis is an iron-dependent mode of cell death distinct from apoptosis and necrosis. Its mechanisms mainly involve disordered iron metabolism, lipid peroxide deposition, and an imbalance of the antioxidant system. The endoplasmic reticulum is an organelle responsible for protein folding, lipid metabolism, and Ca 2+ regulation in cells. It can be induced to undergo endoplasmic reticulum stress in response to inflammation, oxidative stress, and hypoxia, thereby regulating intracellular environmental homeostasis through unfolded protein responses. It has been reported that ferroptosis and endoplasmic reticulum stress (ERS) have an interaction pathway and jointly regulate cell survival and death. Both have also been reported separately in rheumatoid arthritis (RA) mechanism studies. However, studies on the correlation between ferroptosis and ERS in RA have not been reported so far. Therefore, this paper reviews the current status of studies and the potential correlation between ferroptosis and ERS in RA, aiming to provide a research reference for developing treatments for RA.